Linking the depletion of rhizosphere phosphorus to the heterologous expression of a fungal phytase in Nicotiana tabacum as revealed by enzyme-labile P and solution 31P NMR spectroscopy - Giles, Courtney D.; George, Timothy S.; Brown, Lawrie K.; Mezeli, Malika; Shand, Charles A.; Richardson, Alan E.; Mackay, Regina; Wendler, Renate; Darch, Tegan; Menezes-Blackburn, Daniel; Cooper, Pat; Stutter, Marc I.; et al. (Rhizosphere, 2017)
Root exudation of phytase could improve the ability of plants to access organic forms of soil phosphorus (P), thereby minimizing fertilizer requirements and improving P use efficiency in agroecosystems. After 75 days growth in a high available P soil, shoot biomass and P accumulation, soil pH, and rhizosphere P depletion were investigated in Nicotiana tabacum wild-type and transgenic plant-lines expressing and exuding Aspergillus niger phytase (ex::phyA), or a null-vector control. Solution 31P NMR analysis revealed a 7% to 11% increase in orthophosphate and a comparable depletion of undefined monoester P compounds (-13 to -18%) in the rhizosphere of tobacco plants relative to the unplanted soil control. Wild-type plants had the greatest impact on the composition of rhizosphere P based on the depletion of other monoester P, polyphosphate, and phosphonate species. The depletion of phytase-labile P by ex::phyA plants was associated with decreased proportions of other monoester P, rather than myo-InsP6 as expected. Rhizosphere pH increased from 6.0 to 6.5-6.7 in transgenic plant soils, beyond the pH optimum for A. niger phyA activity (pH=5), and may explain the limited specificity of ex::phyA plants for phytate in this soil. The efficacy of single exudation traits (e.g., phytase) therefore appear to be limited in P-replete soil conditions and may be improved where soil pH matches the functional requirements of the enzyme or trait of interest. [Display omitted]